Allergic rhinitis - Noor Al-Huda Sabih Eidan Meehbis; Yousif Jawad Abdulkadhim Mahsan; Amjed Abdul-Abbas Sayah Gaffl; Kawthar Amer Shanati Muhammad (Genius Journals, 2024)
Allergic rhinitis is caused by a reaction of the body's immune system to an environmental irritant. The most common environmental irritants include dust, mold, pollen, hay, trees, and animals. Both seasonal allergies and year-round allergies can cause allergic rhinitis. Symptoms of allergic rhinitis include itching, sneezing, nasal congestion, runny nose, itching, and watery eyes. The patient may also suffer from headache, swollen eyelids, coughing, and wheezing, and the doctor can diagnose allergic rhinitis based on a history of medical symptoms. In many cases, the patient has The person has a family history of allergies. The doctor may be able to obtain more detailed information from blood tests or skin tests
Keywords: Allergic; rhinitis; dust; mold